2004
DOI: 10.1021/np040138l
|View full text |Cite
|
Sign up to set email alerts
|

Iridoid Glucosides and p-Coumaroyl Iridoids from Viburnum luzonicum and Their Cytotoxicity

Abstract: Four new iridoids glucosides (1-4) and seven new iridoid aglycons (5-11) bearing (E)- or (Z)-p-coumaroyl groups were isolated from a methanol extract of the dried leaves of Viburnum luzonicum collected in Kaoshiung, Taiwan. The structures of the new compounds, named luzonoside A (1), luzonoside B (2), luzonoside C (3), luzonoside D (4), luzonoid A (5), luzonoid B (6), luzonoid C (7), luzonoid D (8), luzonoid E (9), luzonoid F (10), and luzonoid G (11), were elucidated by analysis of spectroscopic data and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…Although some of the tested flavonoids did not show a cytotoxicity in the present assay against MT-4 cells, some of them have been however shown to be toxic to a number of tumor cell lines supporting thus their important role in the prevention of prostate, breast, and colon cancers (Gâlvez et al, 2003;Kobayashi et al, 2002;Le Bail et al, 1998) or against human leukemia cell line HL-60 (Sonoda et al, 2004). The four new iridoids isolated from Morinda morindoides did not show a cytototoxic effect against MT-4 cells and this is in good agreement with Murakami et al (2002) who reported the same effect for other iridoids against the same cell-lines However, other types of iridoids isolated from other plant species have been reported to be toxic against different cell lines (Fukuyama et al, 2004(Fukuyama et al, , 2005Kumarasamy et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…Although some of the tested flavonoids did not show a cytotoxicity in the present assay against MT-4 cells, some of them have been however shown to be toxic to a number of tumor cell lines supporting thus their important role in the prevention of prostate, breast, and colon cancers (Gâlvez et al, 2003;Kobayashi et al, 2002;Le Bail et al, 1998) or against human leukemia cell line HL-60 (Sonoda et al, 2004). The four new iridoids isolated from Morinda morindoides did not show a cytototoxic effect against MT-4 cells and this is in good agreement with Murakami et al (2002) who reported the same effect for other iridoids against the same cell-lines However, other types of iridoids isolated from other plant species have been reported to be toxic against different cell lines (Fukuyama et al, 2004(Fukuyama et al, , 2005Kumarasamy et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the presence of terpenes as major components in the ethyl acetate extract may explain its high cytotoxic activity. In fact, the anti-cancer potential of these products has been recently reported (23)(24)(25)(26). The molecular mechanisms of these purified components have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Iridoid glucosides 181 and 182 and their aglycones (185-189) exhibited moderate inhibitory activity with IC 50 values of 3-7 mM, whereas compound 183 and 184 showed no cytoxicity even at 100 mM. 84) Furthermore, cytotoxic iridoids 181, 182 and 185-189 also inhibited the growth and the cell viability in primary-cultured rat cortical neurons at 10 mM. and all these compounds showed weak cytostatic/cytotoxic activity (GI 50 : 1-9 mg/ml) against cancer cell lines, HM02 (stomach carcinoma), Hep G2 (liver carcinoma) and MCF7 (mamma carcinoma) according to NCI-directives.…”
Section: )mentioning
confidence: 99%